Cells in somatosensory areas show synchrony with beta oscillations in monkey motor cortex - Witham, Claire L (Blackwell Publishing Ltd, 2007)
Oscillatory synchronization between somatosensory and motor cortex has previously been reported using field potential recordings, but interpretation of such results can be confounded by volume conduction. We examined coherence between single-unit discharge in somatosensory/parietal areas and local field potential from the same area as the unit, or from the motor cortex, in two macaque monkeys trained to perform a finger movement task. There were clear coherence peaks at ∼17.5 Hz for cells in the primary somatosensory cortex (both proprioceptive and cutaneous areas) and posterior parietal cortex (area 5). The size of coherence in all areas was comparable to previous reports analysing motor cortical cells and M1 field potentials. Many coherence phases clustered around –π/2 radians, indicating zero lag synchronization of parietal cells with M1 oscillatory activity. These results indicate that cells in somatosensory and parietal areas have information about the presence of oscillations in the motor system. Such oscillatory coupling across the central sulcus may play an important role in sensorimotor integration of both proprioceptive and cutaneous signals.